Global Phylogenomic Analysis of Nonencapsulated Streptococcus pneumoniae Reveals a Deep-Branching Classic Lineage That Is Distinct from Multiple Sporadic Lineages. (24th December 2014) - Hilty, Markus; Wüthrich, Daniel; Salter, Susannah J; Engel, Hansjürg; Campbell, Samuel; Sá-Leão, Raquel; de Lencastre, Hermínia; Hermans, Peter; Sadowy, Ewa; Turner, Paul; Chewapreecha, Claire; Diggle, Mathew; et al.
Abstract: The surrounding capsule of Streptococcus pneumoniae has been identified as a major virulence factor and is targeted by pneumococcal conjugate vaccines (PCV). However, nonencapsulated S. pneumoniae (non-Ec- Sp ) have also been isolated globally, mainly in carriage studies. It is unknown if non-Ec- Sp evolve sporadically, if they have high antibiotic nonsusceptiblity rates and a unique, specific gene content. Here, whole-genome sequencing of 131 non-Ec- Sp isolates sourced from 17 different locations around the world was performed. Results revealed a deep-branching classic lineage that is distinct from multiple sporadic lineages. The sporadic lineages clustered with a previously sequenced, global collection of encapsulated S. pneumoniae (Ec- Sp ) isolates while the classic lineage is comprised mainly of the frequently identified multilocus sequences types (STs) ST344 ( n = 39) and ST448 ( n = 40). All ST344 and nine ST448 isolates had high nonsusceptiblity rates to β-lactams and other antimicrobials. Analysis of the accessory genome reveals that the classic non-Ec- Sp contained an increased number of mobile elements, than Ec- Sp and sporadic non-Ec- Sp . Performing adherence assays to human epithelial cells for selected classic and sporadic non-Ec- Sp revealed that the presence of a integrative conjugative element (ICE) results in increased adherence to human epithelial cells ( P = 0.005). In contrast, sporadic non-Ec- Sp lacking the ICE had greater growth in vitro possibly resulting in improved fitness. In conclusion, non-Ec- Sp isolates from the classic lineage have evolved separately. They have spread globally, are well adapted to nasopharyngeal carriage and are able to coexist with Ec- Sp. Due to continued use of PCV, non-Ec- Sp may become more prevalent.